Synergistic effects of NPN transistors caused by combined proton irradiations with different energies. (March 2018) - Li, Xingji; Yang, Jianqun; Liu, Chaoming; Bai, Gang; Luo, Wenbo; Li, Pengwei
Abstract: There are a large number of protons with different energies from the dozens of keV to hundreds of MeV in space environment, which simultaneously act on the bipolar junction transistors (BJTs), and induce different irradiation effect and damage defects. Moreover, interaction between displacement defects and ionization defects occurs. In the paper, the interaction mechanisms between oxide charge and displacement defects in 3DG112 NPN BJTs caused by the combined 70 keV and 170 keV protons with 5 MeV proton irradiation are studied. Experimental results show the degradation of current gain increases linearly with increasing the irradiation fluence of the 170 keV and 5 MeV protons, but increases nonlinearly for the 70 keV protons, implying that the 170 keV and 5 MeV protons mainly induce displacement damage on the NPN BJTs, while the 70 keV protons cause ionization damage. It can be seen from the Geant4 calculation that 70 keV and 170 keV protons cause almost the same ionization damage on the 3DG112 transistors, while have significant difference in displacement damage ability, which is favorable to analyze the effect of displacement damage in oxide layer of NPN BJTs induced by 170 keV and 70 keV protons on ionization damage caused by the subsequent 5 MeV protons. DLTS analyses show that 5 MeV protons produce mainly displacement defect centers in based-collector junction of 3DG112 transistors, and 170 keV and 70 keV protons only induce almost the same number of the oxide trapped charges. While the combined irradiation can produce the more oxide trapped charges, except displacement defects, showing that displacement damage in oxide layer caused by 170 keV and 70 keV protons can increase the oxide trapped charges during the subsequent 5 MeV exposures. Moreover, the more displacement defects in oxide layer will induce more oxide trapped charges, and give more enhanced synergistic effects. These results will help to assess the reliability of BJTs in the space radiation environment. Highlights: Synergistic effects of NPN transistors caused by combined proton irradiations with different energies is studied. The combined irradiation experiments show that displacement damage in oxide layer can increase the oxide trapped charges during the subsequent exposures. The more displacement defects in oxide layer will induce more oxide trapped charges, leading to more enhanced synergistic effects.